Suitability of Kabanyolo Soils for Fruit and Vegetable Production - Okiror, Paul; Bahati, Joseph; Lejju, Julius Bunny; Rugunda, Grace Kagoro; Sebuuwufu, Collins Inno; Patrick Mulindwa; Jolly Joe Ocan (Scientific Research Publishing inc., 2017)
This paper presents results of soil analysis for samples extracted from Makerere University Agricultural Research Institute Kabanyolo. The study was aimed at ascertaining the suitability of MUARIK soils for fruit (pineapple, passion fruit and watermelon) and vegetable (cabbage, eggplant, tomato and pumpkin) growth, yield and maturity. Soil morphological, physical and chemical properties were probed by excavating a 1.86 meter soil profile pit and sampling soils in 9 equidistant locations at MUARIK. The soil morphology and physical properties were described using the Munsel colour chart and USDA classification system while chemical parameters were determined in Makerere University Soil Laboratory following procedures described by Okalebo et al. [1]. Three pedon layers (RSK-H1, RSK-H3 and RSK-H5) had gradual boundaries while RSK-H4 was continuous. However, RSK-H2 and RSK-H6 had abrupt boundary layers. The texture of the profiles was clayey (52%). The soils were acidic with a pH of 6.08 (sub soil) to 6.12 (top soil). On comparison with standard requirements for target fruits and vegetables, the site was deficient in most of the minerals including P (8.88 - 12.42 pmm), Ca (6.46 - 7.92 pmm), K (0.06 - 0.47 pmm), Mg (1.37 - 1.70 pmm), Na (0.17 - 0.23 pmm), N (0.18 - 0.19 pmm), and soil organic matter (4.53% - 4.81%). Sand and clay had the highest negative significant correlation (r = −0.94, p < 0.01) in the top soil. The highest positive significant correlation was observed between Ca and Mg both in the topsoil (r = 0.96, p < 0.01) and subsoil (r = 0.99, p < 0.01). MUARIK is suitable for growing cabbage and pumpkin. However, for improved growth, yields and maturity, the soils should be amended with manure (watermelon), lime (passion fruit and tomato) and sulphur (eggplant and pineapples).
Suitable soils for Fruits and Vegetables at Kabanyolo
Keywords: soils, Fruit and Vegetable, Kabanyolo, suitability